WORKSHOP MANAGEMENT MAPPING IN ELECTRICAL MAINTENANCE SUBJECTS OF LIGHT VEHICLE ELECTRICITY PRACTICUM IN VOCATIONAL SECONDARY SCHOOL - Dinulloh, Fabela; Sukrawan, Yusep; Permana, Tatang (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2021)
The present study aims to determine how the availability of practical tools on Subjects Electric Light Vehicle Maintenance at SMKN in Cianjur city and the ratio of the number of laboratory infrastructure with the number of learners, where ideally at the time doing practical comparison between a practice tool with learners is one to one, it may cause delays in the lab so that it requires a relatively long time (over time). The research method using quantitative descriptive method, while the technique of collecting data, observation and documentation. The population of this study is Repair Light Vehicle Engineering SMKN in Cianjur City, The sample of this research is a practical workshop Electric Light Vehicle Maintenance SMKN in Cianjur city. The results showed in general that means practicum in a category worthy, lab infrastructure in less worthy category, the ratio of the number of facilities and infrastructure with a number of students in a category is not feasible.